Study Of The Mass Construction Of Al Irsyad Mosque In The Kota Baru Parahyangan - Andiyan Andiyan; Firmansyah Firmansyah (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2022)
Al Irsyad Mosque is situated in Bandung, Indonesia, in Kota Baru Parahyangan, Padalarang. The construction of this mosque started on September 7, 2009, and was completed a year later. This mosque is modeled after the Kaaba in Makkah's Grand Mosque. This mosque was named one of the five finest buildings in the world in 2010 by the National Frame Building Association in the area of "religious architecture." This mosque is a work of modern architecture that succeeds in breaking the mold of most mosque shapes. Contemporary architecture is defined as a new, contemporary, distinctive, and original piece of architecture, regardless of its visual design, style, or theme. This course discusses descriptive qualitative research. This research is about modern architecture, as defined by many characteristics. The building's expression is subjective, contrasts with its surroundings, emphasizes a distinctive form, is out of the ordinary, and is appealing. The study's findings are anticipated to explain the use of modern architectural ideas at the Al Irsyad Mosque.